Tingkat Pengetahuan Remaja Putri Pada Penanganan Dismenorea Primer Dengan Kompres Hangat - Elvika Fit Ari Shanti; Leni LuvitaYanuarti (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2015)
Background: 75% of Indonesian women have ever used femininity liquid cleaning soap that was In Indonesia,55% of productive woman had tormented by dysmenorrhoea, with pravelence ranging from 45-95% in productiveage (Proverawati and Misaroh, 2009). The womenhad dysmenorrhoea more bad in achievement than the womenhad not dysmenorrhoea. The usage of warm compresses were a way to eliminated or decreaced the pain withoutside effetcts.Objective: Knowing the knowledge of young women in the handling of primary dysmenorrhoea with warm compresses in especially include menstruation comperhension, the cause of dysmenorrhoea, dysmenorrhoea indication, and handling of primary dysmenorrhoea.Method: Descriptive as the kind of research with survey in approach. The research population amounted to 50respondents was all young women in Class XI IPA of 1 Mlati Senior High School, Sleman,. The sampling techniqueof sample. The tool of collection used questionnaires. The data analysis used univariant and described in precentage.Results: The young women knowledge about handling of primary dysmenorrhoea with warm compresses weremostly good category (76%), that includes about menstruatuon comperhension were mostly good category (100%),dysmenorrhoea comperhension were mostly good category (70%), the cause of dysmenorrhoea were mostly lesscategory (64%), dysmenorrhoea indication were nostly less category (60%), handling of primary dysmenorrhoeawere mostly good category (76%).Conclusion: The young women knowledge about handling of primary dysmenorrhoea with warm compresses inClass XI IPA in 1 Mlati Senior High School, Sleman, Yogyakarta were good at 76%.Keywords: The knowledge, young women, primary dysmenorrhoea, warm compresses.